Toxicity in vitro reveals potential impacts of microplastics and nanoplastics on human health: A review. Issue 21 (2nd November 2022) - Shi, Qingying; Tang, Jingchun; Liu, Rutao; Wang, Lan
Abstract: Microplastics (MPs) have attracted considerable interest on account of their ubiquitous presence in the environment in recent years. In particular, nanoplastics (NPs), with smaller sizes, seem to obtain more attention due to their unique physical and chemical properties. Humans are inevitably exposed to MPs and NPs, whereas the potential adverse effects on human health have been little explored. In this review, we provided a systemically overview of recent in vitro studies related to the impacts of MPs and NPs on human health. The uptake mechanisms of MPs and NPs and affecting factors at the cellular level were first discussed. The toxic effects of plastic particles themselves as well as the cytotoxic mechanisms of MPs and NPs were elaborated subsequently. Furthermore, we summarized the toxicity of adhering contaminants and plastic leachates. In general, the MPs and NPs exert adverse effects in various cell types through multiple toxic mechanisms. Nonetheless, challenges on MPs and NPs toxicity still remain hindering the risk assessment on human health. Key challenges and further research needs are also suggested in this review as more studies are needed to perform and explore the potential impacts of MPs and NPs on human health in the future. Graphical abstract: UF0001